Analysis of Scooter Taxi User Satisfaction from the Aspect of Usability Through the Maxride Application in Makassar Using the Use Questionnaire Method - Achmad, Muh Fachran Fahiran; Saleh, Anis; Hafid, Muhammad Fachry (Omnia Tempus, 2023)
This study aims to analyze the usability of the Maxride ride-hailing application in Makassar, Indonesia, focusing on user satisfaction from a usability perspective. The research employed a quantitative approach using the USE Questionnaire method. Data was collected from 400 Maxride users in Makassar through an online survey. The questionnaire assessed four usability variables: Usefulness, Ease of Use, Ease of Learning, and Satisfaction.The overall usability score of the Maxride application was 65.60%, falling in the